Temperature dependent magnetoelectric coupling in BaTiO3/La0.67Sr0.33MnO3 heterojunction. (7th March 2018) - Wang, Jianyuan; Bai, Jianying; Han, Zhuokun; Jin, Kexin; Chen, Changle; Zhai, Wei
Abstract: The polarization and dielectric properties in a BaTiO3 /La0.67 Sr0.33 MnO3 (BTO/LSMO) heterojunction with external magnetic field are investigated in the temperature range from 20 to 300 K. Excited by magnetic field under an intensity of 0.8 T, the saturation polarization is enhanced by a maximum value of 21.5% at 220 K, and the coercive electric field is decreased by a peak rate of 10.5% at 200 K. There also exists a significant magneto-induced variation of dielectric property around the temperature range of 200–220 K. The maximum changing rate of the dielectric constant and dielectric loss reaches 23.6% and 17.9%, respectively. The temperature range with the above maximum magnetoelectric coupling effect is consistent with the metal-insulator transition temperature of the LSMO layer. The magneto-induced polarization and dielectric performance change may result from the charge-based coupling through the BTO/LSMO interface.